Learning in an industrial practicum training program: a case study in a public university in Malaysia - Mohd Shariff, Sariwati; Muhamad, Mazanah (IDOSI Publications, 2010)
This study investigates on the learning processes and learning outcomes from the undergraduates’ perspectives after completion of their practicum attachment in the industry. Adopting a qualitative design approach, in depth interviews were carried out on 12 students, specifically from the Operations Management Program, Faculty of Business Management of a local public university in Malaysia. Learning in the practicum training was evidenced through various learning processes as described by the informants such as: learning through observing, doing authentic tasks, problem solving, social interactions, experiences and through feedbacks. This study revealed that these trainees acquired job-related knowledge (cognitive outcomes), developed related work and hands on skills (psychomotor outcomes) and acquired work values at their workplaces. However, there are areas for improvement to enhance the quality of practicum training such as the curricular structure of the industrial training program, proper placement of undergraduates and guidelines for practicum training for both the students and the organization so as to enhance the human capital development of these potential new executives for the global business in the future.